PENIPUAN PENGGUNAAN ALAT ANTIGEN BEKAS (Studi Kasus Bandara Kualanamu, Medan-Sumut) - Gomgom T.P Siregar; Lestari Victoria Sinaga; Andrie Ghaivany Purba (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
One form of structured consumer fraud during the COVID-19 pandemic is the crime of using used antigen devices which has an impact on Article 196 of Law Number 36 of 2009 concerning Health in conjunction with Article 55 of the Criminal Code, where anyone who intentionally produces pharmaceutical preparations does not meet the standards. and quality shall be sentenced to a maximum imprisonment of 10 years and a maximum fine of Rp. 1.000.000.0000,-. This research uses normative juridical research, namely examining the laws and regulations, namely Law Number 36 Year 2009 concerning Health and the Criminal Code. The formulation of the problem is that the police are asked to thoroughly investigate the fraudulent use of this used antigen device and not stop at the perpetrators in the field. In addition to the health sector, the purpose of protection against the threat of Covid-19 is where the government saves health and social security by issuing a circular letter from the task force for handling coronavirus disease number 7 of 2021 concerning the extension of travel provisions for domestic people during the coronavirus disease pandemic which determines that everyone If you want to travel by airplane, you must show a certificate of negative rapid test result-Polymerase Chain Reaction, hereinafter referred to as RT-PCR or negative result of rapid antigen test. Due to these conditions, medical officers and the government must provide health facilities and the need for RT PCR or rapid antigen tests is a business opportunity in the health sector, especially the price is quite expensive so that this condition is carried out by Kimia Farma medical officers who intentionally recycle the antigen rapid test kit. The former occurred at Kualanamu Airport, Medan City, North Sumatra.